Methicillin-Resistant Staphylococcus epidermidis (MRSE): An Updated Narrative Review on its Epidemiology, Resistance Mechanisms, and Emerging Treatment Strategies - Ghosh, Sourav; Singh, Shelly; Kaushik, Priya (Anti-Infective Agents, 2026)
IntroductionPatients with indwelling medical devices and those with impaired immune systems are the primary targets of methicillin-resistant Staphylococcus epidermidis (MRSE), a common infection linked to healthcare. Its gram-positive nature and ability to develop biofilms make it the causative agent of more than 30% of coagulase-negative Staphylococcus (CoNS) infections.ObjectiveThis narrative review provides an overview of the epidemiology, mechanisms of resistance, clinical significance, and emerging treatment strategies for MRSE, with a particular focus on recent advancements in infection prevention and control.MethodsA comprehensive narrative review of literature published between 2010 and 2024 was conducted using PubMed, Scopus, and Web of Science. MeSH terms and free text keywords that would be relevant to the study have been used accordingly to identify studies of MRSE epidemiology, resistance mechanisms, infection control, and therapeutic interventions.Results and DiscussionWith outbreaks connected to clonal complexes CC5 and CC8, the incidence of MRSE has risen by about 25% in North America and Europe and by 35% in Asia over the last ten years. Incident rates are close to 40% among high-risk groups, especially those receiving immunosuppressive treatment or extended hospital stays. Methicillin resistance is caused by the mecA gene, which makes treatment more difficult. Dalbavancin and oritavancin are two examples of novel antimicrobials that have demonstrated clinical efficacy, lowering infection rates by as much as 20%. In high-risk environments, the use of improved infection control techniques has reduced transmission by about 15%. Antimicrobial peptides and bacteriophage-based treatments are two promising research directions.ConclusionInfection control in hospital settings is severely hampered by the increasing frequency and antibiotic resistance of MRSE. To lessen its clinical impact and enhance therapeutic results, more research and the application of strong infection control procedures are necessary.
Keywords: nosocomial